RNA interference revolution - Thakur,Archana (Pontificia Universidad Católica de Valparaíso, 2003)
RNA interference (RNAi) is a potent method using only a few double stranded RNA (dsRNA) molecule per cell to silence the expression which has made it one of the hottest topics in molecular biology in last two years. Not long ago scientists conducted gene knock out using antisense, dominant negative or knockout techniques which were ineffective, but the discovery of RNAi has enabled to knock out gene in any organism efficiently. RNA silencing was first discovered in transgenic plants, where it was termed co-suppression or post transcriptional gene silencing (PTGS). Five years ago the evidence for RNA silencing emerged from experimental observation on Caenorhabditis elegans, this new approach for achieving efficient, targeted gene silencing is now making its way beyond laboratory notebooks into biotech strategic plans. Its a phenomenon of gene silencing which offers a quick and easy way to determine the function of a gene. Its a natural catalytic process and an intrinsic property of every cell of every multicellular organism. Reported to be 1,000-fold more effective than antisense. The new field of RNAi based genomics is increasingly being qualified as a fundamental paradigm shift for biomedical research and development and quite possibly the start of a veritable revolution for the development of modern therapeutics.